A Smartphone-Based Timed Up and Go Test Self-Assessment for Older Adults: Validity and Reliability Study - Melissa Johanna Böttinger; Sabato Mellone; Jochen Klenk; Carl-Philipp Jansen; Marios Stefanakis; Elena Litz; Anastasia Bredenbrock; Jan-Philipp Fischer; Jürgen M Bauer; Clemens Becker; Katharina Gordt-Oesterwind (JMIR Aging)
Abstract BackgroundThe Timed Up and Go test (TUG) is recommended as an evidence-based tool for measuring physical capacity. Instrumented TUG (iTUG) approaches expand classical supervised clinical applications offering the potential of self-assessment for older adults. ObjectiveThis study aimed to evaluate the concurrent validity and test-retest reliability of a smartphone-based TUG self-assessment “up&go app.” MethodsA total of 52 community-dwelling older adults (>67 years old) were recruited. A validated and medically certified system attached with a belt at the lower back was used as a reference system to validate the “up&go app” algorithm. The participants repeated the TUG 5 times wearing, a smartphone with the “up&go app” in their front trouser pocket and an inertial sensor to test the concurrent validity. A subsample of 37 participants repeated the “up&go app” measurement 2 weeks later to examine the test-retest reliability. ResultsThe correlation between the “up&go app” and the reference measurement was rr ConclusionsThe duration of 5 repetitions of the TUG test, measured with the pocket-worn “up&go app,” was very consistent with the results of a lower-back sensor system, indicating excellent concurrent validity. Participants walked slower in the first round than in the other 4 repetitions within a test run. Test-retest reliability was also excellent. The “up&go app” provides a useful smartphone-based approach to measure 5 repetitions of the TUG. The app could be used by older adults as a self-screening and monitoring tool of physical capacity at home and thereby help to early identify functional limitations and take interventions when necessary.